COVID-19 Perceptions, Avoidance and Vaccine Attitudes of Nursing Students: Case of Türkiye - ULAŞ KARAAHMETOĞLU, Gülşen; ARABACI, Zeynep (E-Journal of Dokuz Eylul University Nursing Faculty, 2024)
Objective: This study was carried out to investigate the factors related to the attitudes of nursing students to avoid COVID-19, their perceptions of the disease, and their attitudes towards the vaccine. Methods: The study used a descriptive cross-sectional study design. Nursing students (n = 354) studying at a university in Turkey formed the sample. Online forms included the descriptive characteristics survey form, the avoidance from COVID-19 attitudes scale, the COVID-19 disease perception scale and the COVID-19 vaccine attitudes scale. Results: The students’ mean COVID-19 disease perception scale dangerousness subscale score was 3.86 ± 0.77 and mean contagiousness subscale score was 3.73 ± 0.99. The students’ mean avoidance from COVID-19 attitudes scale cognitive avoidance subscale score was 2.29 ± 0.92 and mean behavioral avoidance subscale score was 3.40 ± 1.04. the students’ mean COVID-19 vaccine attitudes scale positive attitude subscale score was 3.62 ± 1.08 and mean negative attitude subscale score was 3.42 ± 0.89. the women had higher scores than the men (p
Keywords: 3. Good health